A causal association between obesity and constipation: a two-sample bidirectional Mendelian randomization study and meta-analysis - Sun, Xian; Zhang, Shuoqiu; Zhou, Xi (Frontiers in Nutrition, 2024)
Based on observational studies, obesity is probably related to constipation, while existing results are conflicting. Therefore, Mendelian randomization (MR) study and meta-analysis were used for performing the causal correlation of obesity with constipation risk.Methods: Independent genetic variants closely related to constipation were acquired from genome-wide association study (GWAS) in this study to analyze the association of genetically-predisposed obesity with the constipation risk. Waist circumference (WC), hip circumference (HC), waist-to-hip ratio (WHR), and body mass index (BMI) were collected from GWASs. Then, the causality of constipation with obesity was explored with two-sample MR study in both directions. The robustness of the results was evaluated by sensitivity analysis. Furthermore, systemic review and meta-analysis were performed to calculate relative risks (RRs) with corresponding 95% confidence intervals (95% CIs). Subgroup analyses stratified by age and obesity degree were completed. To evaluate whether the current studies were affected by unmeasured confounders, E-values of different studies were determined.